The Application Of Subcutaneous Insulin Therapy To Overcome Hyperglycemia In Diabetes Mellitus Patients Through The Implementation Of Orem's Theory At Bhayangkara Hospital Bengkulu In 2025 - Khasanah, Uswatun; Tranado, Hengki (Utami Publisher, 2026)
Diabetes Mellitus is a metabolic condition in which blood glucose levels exceed the normal range. The increase in blood glucose levels is caused by impaired insulin secretion, insulin function, or both (Prihatin, 2019). Subcutaneous insulin therapy is a method of insulin administration in which insulin is injected into the subcutaneous fat tissue with the aim of controlling blood glucose levels in individuals with diabetes mellitus.The purpose of this study is to understand and apply nursing care in the implementation of subcutaneous insulin therapy to manage hyperglycemia in patients with diabetes mellitus through the application of Orem’s Theory at Bhayangkara Hospital Bengkulu in 2025, by providing nursing care for three days.The results obtained after implementing subcutaneous insulin therapy in Mrs. A and Mrs. N showed a decrease in random blood glucose levels over the three-day intervention period.It can be concluded that the implementation of subcutaneous insulin therapy has a significant effect in reducing hyperglycemia in patients with diabetes mellitus.